The teams’ formation in sport aerobics on the basis of application of multidimensional analysis methods - Zh.L. Kozina; T.V. Shepelenko; Miroslawa Cieslicka; Katarzyna Prusik; Radoslaw Muszkieta; A.V. Osiptsov; V.M. Kostiukevych; T.A. Bazilyuk; I.N. Sobko; O.A. Ryepko; S.B. Polishchuk; A.S. Ilnickaya (Physical Education of Students, 2017)
The purpose of the research is to develop the principles of team’s formation in sport aerobics with application of factorial and cluster analysis’ methods. Material: in a research girls (n=24) from the sport aerobics national team (Kharkiv, Ukraine) participated. The athletes were given full medical examination by determination of functional condition of an organism (arterial blood pressure, indicators of a variability of the rhythm of the heart, treadbahn testing), a psycho-physiological condition (time’s determination of simple and complex reaction). It was defined physical development and physical fitness and vestibular stability. Results. The mathematical and visual models of each group of athletes were developed. The cluster analysis permitted selection of 8 groups of girls. The athletes of each group can incorporate with each other in teams for different competitive categories. The each group of athletes should select appropriate programs according to the features of their personal factorial structure of fitness. The general recommendations about selection of programs’ story lines for athletes of each group are developed. Conclusions. The possibilities of athletes’ groups formation (in pairs, in trio, in five) for mixed performances are revealed. It is determined that it is possible to select athletes with similar qualities (representatives of one cluster) and with different qualities (representatives of different clusters) for mixed performances.